Model Perubahan Penggunaan Lahan Untuk Mendukung Rencana Pengelolaan Kesatuan Pengelolaan Hutan (Studi Kasus KPH Yogyakarta) - Septiono, Dony Setiawan; Mussadun, Mussadun (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Special Region of Yogyakarta (DIY) experience the dynamics of changes in land use so that the decline in the forest area of the country. The government set the FMU Forest Management Unit as part of efforts to protect the forests remain sustainable so we need a study that could support optimal implementation of the Management Plan Forest Management Unit (FMU RP). One method to support the optimization is to do a land change prediction models. The purpose of this study include: (1) analyze the land use change from 1990 to 2013 period and (2) predicting the year 2023. Changes in land use land studied is 1990 and 2013, which would then be used as a base projection in 2013-2023. Methods to be used are: 1) Analysis of input output, 2) the integration of Markov chain Celullar automata (CA-MC) with logistic regression. The prediction model will use two scenarios, namely: 1) the existing condition of the existing and 2) the assumption of government intervention with the basic rules. The results showed in the period of 1990-2013 there is a change of land use is of 23%, or around 3,703 ha. From the results predicted changes in land use in 2023, with scenario 1 change-forest land dry land agriculture as an area of 1,337 ha and a change of scenario 2 of forest land area of 1264.36 ha.